Toward an urgent yet deliberate conservation strategy: sustaining social-ecological systems in rangelands of the Northern Great Plains, Montana - Kathleen Epstein (Resilience Alliance, 2021)
Urgency and deliberateness are often at odds when executing conservation projects, especially as the scale and complexity of objectives increases. The pace of environmental degradation supports immediate and measurable action. However, best practices for adaptive governance and building resilient social-ecological systems call for more deliberate efforts and participatory processes, which can be slow. We explore conflicts between urgency and deliberateness and the potential for their reconciliation through a case study of the challenges of conserving native rangelands in North America's Northern Great Plains, an ecoregion targeted for global conservation initiatives. This region is undergoing a significant social-ecological transition, which underscores a need to rethink conservation strategies in light of the social-ecological system dynamics and potential future trajectories. Based on a structured narrative literature review process and iterative engagement with key regional stakeholders, we identify three interrelated factors critical to the system's future outcomes that illustrate system complexity as well as trade-offs between urgent and deliberate action and unilateral and multilateral approaches to conservation: (1) influences of land management on biodiversity, (2) economic restructuring and shifting land use priorities, and (3) changing climate and disturbance regimes. We identify key gaps in the literature for each factor and across the factors - an effort that informs our call for research and practice agendas that address uncertainty and complexity at regional scales through more inclusive and future-oriented approaches.